2017
DOI: 10.1002/humu.23250
|View full text |Cite
|
Sign up to set email alerts
|

Deficient activity of alanyl-tRNA synthetase underlies an autosomal recessive syndrome of progressive microcephaly, hypomyelination, and epileptic encephalopathy

Abstract: Aminoacyl-transfer RNA (tRNA) synthetases ligate amino acids to specific tRNAs and are essential for protein synthesis. Although alanyl-tRNA synthetase (AARS) is a synthetase implicated in a wide range of neurological disorders from Charcot-Marie-Tooth (CMT) disease to infantile epileptic encephalopathy, there have been limited data on their pathogenesis. Here we report loss-of-function mutations in AARS in two siblings with progressive microcephaly with hypomyelination, intractable epilepsy and spasticity. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 27 publications
1
53
1
Order By: Relevance
“…In contrast, other CMT-linked mutations have been reported to cause a loss of charging activity, suggesting that haploinsufficiency of the enzyme may be a possible contributing factor (Griffin et al, 2014; McLaughlin et al, 2012). Supporting this hypothesis, recessive mutations in synthetases have been linked to neurodegenerative disease, as well as many multisystem disorders involving a wider range of tissues, and many of these mutations have been found to reduce aminoacylation activity in vitro (Kodera et al, 2015; McLaughlin et al, 2010; van Meel et al, 2013; Meyer-Schuman and Antonellis, 2017; Nakayama et al, 2017; Puffenberger et al, 2012; Simons et al, 2015; Taft et al, 2013; Wolf et al, 2014; Zhang et al, 2014a). Impaired synthetase function may reduce the amount of charged tRNA available for translation elongation, with a possible increase in the levels of uncharged tRNA.…”
Section: Defects In Aminoacyl Trna Synthetase Function In Neurodegenementioning
confidence: 98%
“…In contrast, other CMT-linked mutations have been reported to cause a loss of charging activity, suggesting that haploinsufficiency of the enzyme may be a possible contributing factor (Griffin et al, 2014; McLaughlin et al, 2012). Supporting this hypothesis, recessive mutations in synthetases have been linked to neurodegenerative disease, as well as many multisystem disorders involving a wider range of tissues, and many of these mutations have been found to reduce aminoacylation activity in vitro (Kodera et al, 2015; McLaughlin et al, 2010; van Meel et al, 2013; Meyer-Schuman and Antonellis, 2017; Nakayama et al, 2017; Puffenberger et al, 2012; Simons et al, 2015; Taft et al, 2013; Wolf et al, 2014; Zhang et al, 2014a). Impaired synthetase function may reduce the amount of charged tRNA available for translation elongation, with a possible increase in the levels of uncharged tRNA.…”
Section: Defects In Aminoacyl Trna Synthetase Function In Neurodegenementioning
confidence: 98%
“…76,77 Finally, patients with SLC1A2 mutations, affecting the glutamate transporter EAAT2, manifest DEE occasionally in tandem with movement disorders such as upper limb dyskinesia. 86,87 Additionally, patients with mutations in WWOX, a gene with a role in apoptosis and tumour suppression, 88 present with treatment-resistant DEE. Patients also often have pronounced dystonia and athetosis.…”
Section: Sodium Channel Genesmentioning
confidence: 99%
“…Specifically, subjects are compound heterozygous for one missense mutation and one null allele, compound heterozygous for two missense mutations, or homozygous for a single missense mutation. 2 Consistent with this notion, functional studies have revealed that recessive disease-associated ARS mutations cause reduced protein abundance in immunoblot assays, [5][6][7][8][9][10][11][12][13][14][15][16][17] decreased mutant enzyme activity via in vitro kinetic assays, 9,[18][19][20][21][22][23][24][25] and/or diminished ability of the mutated gene to support cellular growth in yeast complementation assays. 12,13,21,22,[26][27][28][29][30][31][32][33] As such, impaired protein translation as a consequence of decreased tRNA charging is the most likely molecular mechanism for ARS-mediated recessive disease.…”
mentioning
confidence: 92%